miR-93, miR-373, and miR-17-5p Negatively Regulate the Expression of TBP2 in Lung Cancer - Li, Ye; Liang, Min; Zhang, Yunhui; Yuan, Bing; Gao, Wenchao; Shi, Zhizhou; Bai, Jie (Frontiers in Oncology, 2020)
Abstract: Recently, several miRNAs had been revealed to play the critical roles in oncogenesis and tumor progression of many cancers. Thioredoxin-1 (Trx-1) binding protein-2 (TBP-2) is an internal inhibitor of Trx-1, which plays the roles in regulating oxidative stress, inhibiting cell growth, promoting apoptosis. The expression of TBP-2 is usually decreased in cancer tissues. However, whether the miRNAs regulate theTBP-2 expression in lung cancer is still unclear. In this study, we examined the levels of TBP-2, miR-93, miR-373 and miR-17-5p in lung cancer tissues and their adjacent normal lung tissues of 36 patients. We found that the expressions of miR-93, miR-373 and miR-17-5p were higher, whereas the expression of TBP-2 mRNA and protein was significantly lower in lung cancer tissues compared with adjacent normal lung tissues. After the three miRNAs mimics were transfected in the lung cancer cells, NCI-H460, the level of TBP-2 mRNA and TBP-2 protein was decreased. Then the anti-cancer drug, 5-fluorouracil was used to stimulate the NCI-H460 cells, the mRNA levels of miR-93, miR-373 and miR-17-5p were decreased, and the level of TBP-2 mRNA and protein was increased. Collectively, the above results suggest that miR-93, miR-373 and miR-17-5p negatively regulate the TBP-2 expression in lung cancer. This study may provide the therapeutic targets with lung cancer.